Adequação dos espaços públicos abertos com enfoque no conforto térmico em cidade de clima subtropical - Santos, Darllan Fabiani da Silva (2021)
The accelerated urbanization process has contributed to the decrease in the environmental quality of cities by disregarding the human dimension, by occupying the soil in a disorderly manner and by altering the urban landscape. As a consequence, it has influenced the thermal field of the terrestrial surface of urban centers. Currently, open public spaces for leisure have some type of imbalance that compromises thermal comfort and that can reduce the time users spend in these spaces, leaving them idle and / or insecure. This research analyzed, through a case study, 3 scenarios of open public spaces for leisure, located in the city of Erechim / RS, located in a subtropical climate. In this analysis, the environmental variables related to thermal comfort were considered, which are the Heat Index (HI) and Temperature and Humidity Index (THI), in addition to the perception of different age groups of users, with the application of a structured questionnaire for the determination of good practices in open public spaces. These scenarios were characterized and diagnosed, according to their physical aspects, their use and the satisfaction of their users with the use of tools designed for post-occupation evaluation (POE). Based on the data obtained and subsequent analysis it was possible to identify that in the selected open public spaces, the morning period was the most uncomfortable due to the cold and the evening and evening periods were the most comfortable, but with records of discomfort due to the heat in some months and that led to the elaboration of the findings matrix and the diagnostic framework. Therefore, this research aims to contribute to guide future decision-making with regard to the planning of public spaces for leisure, both in the adequacy of existing spaces and in the development of new spaces, and this contribution can be applied not only in city of Erechim, but in cities with a subtropical climate.